2021
DOI: 10.1111/mmi.14703
|View full text |Cite
|
Sign up to set email alerts
|

A single system detects and protects the beneficial oral bacterium Streptococcus sp. A12 from a spectrum of antimicrobial peptides

Abstract: The commensal bacterium Streptococcus sp. A12 has multiple properties that may promote the stability of health-associated oral biofilms, including overt antagonism of the dental caries pathogen Streptococcus mutans. A LanFEG-type ABC transporter, PcfFEG, confers tolerance to the lantibiotic nisin and enhances the ability of A12 to compete against S. mutans. Here, we investigated the regulation of pcfFEG and adjacent genes for a two-component system, pcfRK, to better understand antimicrobial peptide resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…However, in a previous study, we showed that the immunity protein SmbFT of a two-peptide mutacin, SmbAB, can also recognize two other closely related two-peptide lantibiotics, haloduracin and gallolacticin, to provide protection ( 25 ). Furthermore, the MutFEG-type immunity complex is also known to provide protection broadly ( 50 ). Thus, immunity function might not be an issue for our system of expressing the type A-II class of lantibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a previous study, we showed that the immunity protein SmbFT of a two-peptide mutacin, SmbAB, can also recognize two other closely related two-peptide lantibiotics, haloduracin and gallolacticin, to provide protection ( 25 ). Furthermore, the MutFEG-type immunity complex is also known to provide protection broadly ( 50 ). Thus, immunity function might not be an issue for our system of expressing the type A-II class of lantibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…A12. The results indicated that a novel set of genes (e.g., dipeptidase-PrsW-like protease, Ccma ABC transporter, and Man-PTS) was responsible for nisin resistance [46]. With respect to Listeria monocytogenes, a transposon library was used to identify transposants with significantly altered biofilm production levels when compared to a wild-type strain.…”
Section: Amp Resistancementioning
confidence: 99%
“…68 The resistance to antimicrobial peptides has recently been attributed to the regulation of the transporter gene PcfFEG, which improves the ability of S. A12 to compete with S. mutans. 69 Shields et al 70 designed a tool that allows for the monitoring of bacterial growth and the bacterial interaction in situ, differentiating among various bacteria that constitute the oral cavity biofilm. The number of S. mutans colonies after 72 h of monoculture was significantly larger than that of the cocultures with S. gordonii and S. A12.…”
Section: Streptococcus Spp With Potential Anti-caries Inhibitory Acti...mentioning
confidence: 99%
“…The resistance to antimicrobial peptides has recently been attributed to the regulation of the transporter gene PcfFEG, which improves the ability of S . A12 to compete with S. mutans 69 …”
Section: Streptococcus Spp With Potential Anti‐caries Inhibitory Acti...mentioning
confidence: 99%